A novel immense configurations of boost converter for renewable energy application - Maroti, Pandav Kiran; Padmanaban, Sanjeevikumar; Blaabjerg, Frede; Ionel, Dan; Wheeler, Patrick (2018)
A three immense configurations of boost converter for renewable energy application is presented in the paper. The Voltage Lift Switched Inductor (VLSI) structure is pledge to extra high voltage conversion. The proposed work represent the modified high voltage conversion boost converter (MBC) and its three configuration with VLSI module namely, Modified Boost Converter with XL Configuration (MBCVLSIXL), Modified Boost Converter with LY configuration (MBCVLSI-LY) and Modified Boost Converter with XY configuration (MBCVLSI-XY). The advantage of proposed converter configurations are-(i) immense voltage conversion ratio for high voltage and low current renewable energy applications, (ii) single switch topologies, (iii) input inductor to avoid reverse current flow from load to source. The detail mathematical analysis of proposed configurations are done with and without considering the internal voltage drop across the circuit components. The comparative investigation is carried out with existed high voltage conversion ratio topologies. The Matlab simulation results validates the working of proposed MBC configurations.